2019
DOI: 10.1080/0144235x.2018.1548807
|View full text |Cite
|
Sign up to set email alerts
|

Anion photoelectron spectroscopy of protein chromophores

Abstract: Photoactive proteins that efficiently and selectively transfer light energy into a physical response are ubiquitous in nature. The small molecule chromophores that lie at the heart of these processes often exist as closed-shell anions following deprotonation in proton-transfer reactions. This review highlights the important role that anion photoelectron spectroscopy, combined with computational chemistry calculations, is playing in improving our understanding of the electronic structure and relaxation dynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 112 publications
1
32
0
Order By: Relevance
“…Broadening of photoelectron spectra, following photoexcitation of resonances above the detachment threshold, was observed in our study of deprotonated luciferin and infraluciferin ions and has been observed in photoelectron spectra of a range of other similar sized molecular anions recorded by various groups [66][67][68] including our own. 69 The PADs support our interpretation of a resonance: b 2 B 0 across the whole spectrum at all photon energies apart from the feature with eKE B 0.9 eV where b 2 o 0 (Fig. S6, ESI †).…”
Section: Resultssupporting
confidence: 74%
“…Broadening of photoelectron spectra, following photoexcitation of resonances above the detachment threshold, was observed in our study of deprotonated luciferin and infraluciferin ions and has been observed in photoelectron spectra of a range of other similar sized molecular anions recorded by various groups [66][67][68] including our own. 69 The PADs support our interpretation of a resonance: b 2 B 0 across the whole spectrum at all photon energies apart from the feature with eKE B 0.9 eV where b 2 o 0 (Fig. S6, ESI †).…”
Section: Resultssupporting
confidence: 74%
“…Broadening of photoelectron spectra following photoexcitation of resonances in the continuum has been observed in similar sized molecular anions by many other groups 14,30,31 including our own. 11,[32][33][34][35][36][37][38][39][40][41][42] This resonance in PhO − has been observed before 12,14 and assigned to indirect detachment from the S 1 (ππ * ) state of PhO − . The S 0 -S 1 (ππ * ) transition corresponds to promotion of an electron from the HOMO shown in Table 1 to the first antibonding orbital on the phenyl ring system (the LUMO of PhO − ) and therefore has shape resonance character with respect to the D 0 continuum.…”
Section: Photoelectron Spectramentioning
confidence: 83%
“…The active site in photoactive proteins and biomolecules is often a simple, well-defined anionic chromophore 1,2 . For example, one of the most studied biochromophores is that found in the photoactive yellow protein (PYP) 3 , where an anionic thioester derivative (Fig.…”
Section: Introductionmentioning
confidence: 99%